2020
DOI: 10.1002/aoc.5512
|View full text |Cite
|
Sign up to set email alerts
|

Highly dispersed Mn2O3−Co3O4 nanostructures on carbon matrix as heterogeneous Fenton‐like catalyst

Abstract: This work reports the synthesis of various carbon (Vulcan XC‐72 R) supported metal oxide nanostructures, such as Mn2O3, Co3O4 and Mn2O3−Co3O4 as heterogeneous Fenton‐like catalysts for the degradation of organic dye pollutants, namely Rhodamine B (RB) and Congo Red (CR) in wastewater. The activity results showed that the bimetallic Mn2O3−Co3O4/C catalyst exhibits much higher activity than the monometallic Mn2O3/C and Co3O4/C catalysts for the degradation of both RB and CR pollutants, due to the synergistic pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 71 publications
1
8
0
Order By: Relevance
“…With the increasing amount of catalyst dosage, the specific surface area and catalytically active site increases; as a result, the k app of MB increases. [ 38,46–48 ] It was observed that when the amount of catalyst used is 5 mg, the degradation completed within 40 min of the reaction.…”
Section: Resultsmentioning
confidence: 99%
“…With the increasing amount of catalyst dosage, the specific surface area and catalytically active site increases; as a result, the k app of MB increases. [ 38,46–48 ] It was observed that when the amount of catalyst used is 5 mg, the degradation completed within 40 min of the reaction.…”
Section: Resultsmentioning
confidence: 99%
“…The enhanced degradation of MB was attributed to the hampered electron-hole recombination due to the loading of Ag and graphene. Furthermore, the studies regarding the application of modified Mn 2 O 3 in oxidants (such as PMS, ) activation for contaminants removal were also reported [ 84 , 99 , 100 , 101 ]. For example, Saputra et al prepared an egg-shaped core/shell α-Mn 2 O 3 @α-MnO 2 catalyst via a hydrothermal process and investigated the catalytic activity of α-Mn 2 O 3 @α-MnO 2 in heterogeneous Oxone® activation for phenol degradation [ 84 ].…”
Section: Mechanisms Of Pms/pds Activation By Mn(iii) (Oxyhydr)oxidesmentioning
confidence: 99%
“…The amount of and was then increased leading to the enhanced degradation of phenol. The efficient degradation of organic dye pollutants (such as Rhodamine B (RhB) and Congo Red (CR)) by bimetallic Mn 2 O 3 -Co 3 O 4 /carbon catalyst activated Fenton-like reaction was also reported [ 100 ]. The superior reactivity of Mn 2 O 3 -Co 3 O 4 /C catalyst in activation for RB and CR degradation was attributed to the good synergistic effect between Co 3 O 4 and Mn 2 O 3 as well as the interaction between metal oxides and carbon.…”
Section: Mechanisms Of Pms/pds Activation By Mn(iii) (Oxyhydr)oxidesmentioning
confidence: 99%
“… 25,26 At present, there are many studies on the degradation of organic contaminants by Mn/H 2 O 2 systems. 27–29 However, there are few reports on the use of Mn and biochar composites as carbon-based catalysts.…”
Section: Introductionsmentioning
confidence: 99%